(untitled) (Innovaciones Educativas, 2024)
This essay reflects on the subject’s contemplation of the "self" when exporting one’s personal image to social networks with the intention of being accepted. It interpellates the reader through a critical reflection and proposes the approach of a hypothetical prosumer (Toffler, 1980) who brings a version of the "self" with which they identify or try to fit between reality and desire. This is an interdisciplinary and multitextual approach to the way the subject communicates through positive parameters a face, a body and a life (Erikson, 1974; Festinger, 1957; Kaplún, 1998). We observe the recurrence of showing oneself, either with a real and genuine image or manipulated to the point of creating an idealized version (Barker, 2020; Koffermann, 2024). It is proposed to redesign some workshops that aim to promote self-confidence, strengthen acceptance strategies and open up to diversity. Furthermore, an essay format is chosen to analyze the impact of the different versions of the self-image of adolescents in social networks on teacher training in media education (https://www.redalfamed.org/vii-congreso-2024-costa-rica). Constructive discussion will be used to offer guidelines for intervention in both the educational and health fields. The strategies are based on the analysis of the multimodal story that emerges from the definitions with which each subject projects his or her "self".